Tourism and economic growth:a panel data approach - Leitão, Nuno Carlos (2011)
This article focuses on the importance of tourism by investigating the relationship between tourist arrivals and the tourism share in economic growth. The findings are consistent with the literature on tourism. Tourist arrivals have positive impact on economic growth. We also find that bilateral trade and investment output are determinants of economic growth. This paper specifies static and dynamic panel models for the period of 1995-2008 between Portugal and 20 partners. We apply the dynamic panel models to observe serial correlation and the endogeneity of some explanatory variables.